2018
DOI: 10.3892/mmr.2018.9380
|View full text |Cite
|
Sign up to set email alerts
|

C‑C chemokine receptor type 3 gene knockout alleviates inflammatory responses in allergic rhinitis model mice by regulating the expression of eosinophil granule proteins and immune factors

Abstract: The present study aimed to investigate the effects of C-C chemokine receptor type 3 (CCR3) gene knockout on allergic rhinitis (AR) in mice, as well as the underlying molecular mechanisms. Ovalbumin was administrated to CCR3+/+ and CCR3−/− BALB/c mice to establish an AR model. The mice were divided into four groups: i) Normal control (CG), ii) AR model (AR), iii) CCR3 knockout CG (CCR3−/−CG) and iv) AR model with CCR3 knockout (CCR3−/−AR). Histological sections of nasal mucosae were examined by hematoxylin and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Inhibitory effects of a CCR3 antagonist on the eotaxin/CCR3 chemotactic response indicate the key role of the CCR3 pathway in eosinophil chemotaxis [17]. CCR3 knockout has been reported to alleviate eosinophil infiltration and the inflammatory response in an allergic rhinitis murine model [18]. Antagonizing CCR3 resulted in decreased nasal lavage ECP and symptom-relieving effects after allergen challenge, suggesting the therapeutic potential of CCR3-targeting pharmacological interventions for eosinophil-induced allergic inflammation [19].…”
Section: Discussionmentioning
confidence: 99%
“…Inhibitory effects of a CCR3 antagonist on the eotaxin/CCR3 chemotactic response indicate the key role of the CCR3 pathway in eosinophil chemotaxis [17]. CCR3 knockout has been reported to alleviate eosinophil infiltration and the inflammatory response in an allergic rhinitis murine model [18]. Antagonizing CCR3 resulted in decreased nasal lavage ECP and symptom-relieving effects after allergen challenge, suggesting the therapeutic potential of CCR3-targeting pharmacological interventions for eosinophil-induced allergic inflammation [19].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge a link between CCR3 and S100A12 remains uncharacterized; however, activation of CCR3 is able to drive the expression of a number of pro-inflammatory pathways ( Zhu et al., 2018 ) and therefore it is possible that CCR3 may act directly or indirectly on S100A12, although this would need to be directly examined in future mechanistic studies. It is also important to note that when we knocked down levels of CCR3 in OA FLS derived from patients with high SF CCL22 levels, we did not observe an impact on S100A12 expression.…”
Section: Discussionmentioning
confidence: 99%
“…The cytoplasm is of variable color from orange to intense pink, very distinctive and unmistakable. Inside, small granules are observed that contain substances such as the major basic protein (MBP), the eosinophilic cationic protein, and the eosinophilic peroxidase [9]. These substances have a cytotoxic and antibacterial function.…”
Section: Eosinophilic Rhinosinusitismentioning
confidence: 99%